Un juego de espejos: Venises - Escribano Aparicio, Francisco Javier (Revista de Filología Románica, 2009)
In this article, we study the book Venises by the French diplomat, voyager and writer Paul Morand. Using the concept of mixed speech, we will unveil the peculiarities of this work related to the author’s own life (autobiographic speech), to his vocation for books about trips and cities (descriptive speech), and with his perception of Venice as a mythical city, built through memory and the world of art and culture (literary speech).